Bacillus S-Layer-Mediated Innate Interactions During Endophthalmitis - Mursalin, Md Huzzatul; Coburn, Phillip S.; Livingston, Erin; Miller, Frederick C.; Astley, Roger; Flores-Mireles, Ana L.; Callegan, Michelle C. (Frontiers in Immunology, 2020)
Bacillus endophthalmitis is a severe intraocular infection. Hallmarks of Bacillus endophthalmitis include robust inflammation and rapid loss of vision. We reported that the absence of Bacillus surface layer protein (SLP) significantly blunted endophthalmitis severity. Here, we further investigated SLP in the context of Bacillus-retinal cell interactions and innate immune pathways to explore the mechanisms by which SLP contributes to intraocular inflammation. We compared phenotypes of Wild-type (WT) and SLP deficient (∆slpA) Bacillus thuringiensis by analyzing bacterial adherence to and phagocytosis by human retinal Muller cells and phagocytosis by mouse neutrophils. Innate immune receptor activation by the Bacillus envelope and purified SLP was analyzed using TLR2/4 reporter cell lines. A synthetic TLR2/4 inhibitor was used as a control for this receptor activation. To induce endophthalmitis, mouse eyes were injected intravitreally with 100 CFU WT or ∆slpA B. thuringiensis. A group of WT infected mice was treated intravitreally with a TLR2/4 inhibitor at 4 hour postinfection. At 10 hours postinfection, infected eyes were analyzed for viable bacteria, inflammation, and retinal function. We observed that B. thuringiensis SLPs contributed to retinal Muller cell adherence, and protected this pathogen from Muller cell- and neutrophil-mediated phagocytosis. We found that B. thuringiensis envelope activated TLR2 and, surprisingly, TLR4, suggesting the presence of a surface-associated TLR4 agonist in Bacillus. Further investigation showed that purified SLP from B. thuringiensis activated TLR4, as well as TLR2 invitro. Growth of WT B. thuringiensis was significantly higher and caused greater inflammation in untreated eyes than in eyes treated with the TLR2/4 inhibitor. Retinal function analysis also showed greater retention of A-wave and B-wave function in infected eyes treated with the TLR2/4 inhibitor. The TLR2/4 inhibitor was not antibacterial in vitro, and did not cause inflammation when injected into uninfected eyes. Taken together, these results suggest a potential role for Bacillus SLP in host-bacterial interactions, as well as in endophthalmitis pathogenesis via TLR2- and TLR4-mediated pathways.